Mixed convection-radiation in lid-driven cavities with nanofluids and time-dependent heat-generating body - Shulepova, Elena, V; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Springer, 2021)
The cooling process of electronic devices having heat-generating elements is a major challenge allowing to develop electronics industry. Therefore, a creation of novel cooling techniques is an important task that can be solved numerically taking into account the multiparametric character of this problem. The mixed convection heat transfer combined with thermal radiation in a lid-driven cavity filled with an alumina-water nanofluid under the effect of sinusoidal time-dependent heat-generating solid element is studied numerically. The partial differential equations formulated in stream function-vorticity variables are solved by the finite difference method. Effects of the Rayleigh number, Reynolds number, thermal radiation parameter, heater location, volumetric heat flux oscillation frequency and nanoparticles volume fraction on liquid flow and heat transfer are analyzed. It has been found that an addition of nanoparticles leads to reduction of the heater temperature, while convective flow rate decreases also.
Keywords: Mixed convection; Nanofluid; Unsteady heat-generating source; Lid-driven cavity; Finite difference method